Ts-Hsp70 induces protective immunity against Trichinella spiralis infection in mouse by activating dendritic cells through TLR2 and TLR4. - Rui Zhang; Qing Sun; Yi Chen; Ximeng Sun; Yuan Gu; Zhang Zhao; Yuli Cheng; Limei Zhao; Jingjing Huang; Bin Zhan; Xinping Zhu (Public Library of Science (PLoS), 2018)
Trichinellosis is a serious food-borne parasitic zoonosis worldwide. In the effort to develop vaccine against Trichinella infection, we have identified Trichinella spiralis Heat shock protein 70 (Ts-Hsp70) elicits partial protective immunity against T. spiralis infection via activating dendritic cells (DCs) in our previous study. This study aims to investigate whether DCs were activated by Ts-Hsp70 through TLR2 and/or TLR4 pathways.After blocking with anti-TLR2 and TLR4 antibodies, the binding of Ts-Hsp70 to DCs was significantly reduced. The reduced binding effects were also found in TLR2 and TLR4 knockout (TLR2-/- and TLR4-/-) DCs. The expression of TLR2 and TLR4 on DCs was upregulated after treatment with Ts-Hsp70 in vitro. These results suggest that Ts-Hsp70 is able to directly bind to TLR2 and TLR4 on the surface of mouse bone morrow-derived DCs. In addition, the expression of the co-stimulatory molecules (CD80, CD83) on Ts-Hsp70-induced DCs was reduced in TLR2-/- and TLR4-/- mice. More evidence showed that Ts-Hsp70 reduced its activation on TLR2/4 knockout DCs to subsequently activate the naïve T-cells. Furthermore, Ts-Hsp70 elicited protective immunity against T. spiralis infection was reduced in TLR2-/- and TLR4-/- mice correlating with the reduced humoral and cellular immune responses.This study demonstrates that Ts-Hsp70 activates DCs through TLR2 and TLR4, and TLR2 and TLR4 play important roles in Ts-Hsp70-induced DCs activation and immune responses.